The Trends of Fiscal Policy in bearing the financial burden of the government and the Extent Leadership in Iraq during the period 2004- 2014 - عبد اللطيف عماد محمد علي; مجيد عامر عبد الله (Journal of Economics and Administrative Sciences, 2017)
Abstract There has been a heated controversy over the role the financial policy plays and how sufficient it is in affording the financial burden. This burden is known as the operational current expenses which the governments of various countries mainly afford, despite the discrepancy in the government’s economic policy. After the deterioration and deficit in the state budget in all countries nowadays, it was necessary to find an appropriate mechanism so as to achieve the interaction and appropriateness between the main instruments of the financial policy on the realistic level with regard to their economy. This research aims to analyses the relationship between the main instruments of the State policy to encounter the increasing financial burden on the government, where the developing countries’ economy in general and Iraq’s in particular suffers from the financial policy’s inefficacy and feebleness due to the fluctuation of these governments’ policies. In addition, there is a lack of credibility for these governments to achieve a noticeable improvement that could create economic stability; especially most of the decisions made regarding the financial policy tend to be under the influence of policy makers. The study concludes that Iraq has been partially able to afford its operational expenses in spite of the economic, political, social, and security challenges it faced. Further, there was no active financial policy and a clear vision for attempting to diversify the revenue resources to depend on instead of depending on oil as the main source for taking the financial burden. In addition, Iraq economy suffers from a structural imbalance that negatively affects its capacity to diversify the revenues resources, while the financial policy has a significant place among other policies because it can play the greatest role in achieving the multiple objectives and thus achieve economic stability.